7-2n=n-143

Simple and best practice solution for 7-2n=n-143 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-2n=n-143 equation:


Simplifying
7 + -2n = n + -143
Reorder the terms:
7 + -2n = -143 + n
Solving
7 + -2n = -143 + n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-1n' to each side of the equation.
7 + -2n + -1n = -143 + n + -1n
Combine like terms: -2n + -1n = -3n
7 + -3n = -143 + n + -1n
Combine like terms: n + -1n = 0
7 + -3n = -143 + 0
7 + -3n = -143
Add '-7' to each side of the equation.
7 + -7 + -3n = -143 + -7
Combine like terms: 7 + -7 = 0
0 + -3n = -143 + -7
-3n = -143 + -7
Combine like terms: -143 + -7 = -150
-3n = -150
Divide each side by '-3'.
n = 50
Simplifying
n = 50

You can always share this solution

See similar equations:

| 2a+6=35 | | 8(x+2)=64 | | 12-6w=10-5w | | 4(3x+5)=10x+2 | | 9x-55+3x+35=180 | | 2(x+10)-6=2 | | 25x-1=9 | | -8m+1-m=12+7 | | 40=64t-16t^2 | | 2y+3+2y=y+6 | | 0=x^4+8x^3-9x^2 | | (3x+7+3x+7)+(4x-2+4x-2)= | | 0.5= | | 2.5+1.3=1.3h-2.3 | | 0.75(8+2y)=3 | | -7(x+2)-43=6-14 | | 12x-3(-4x+3)+5=13 | | -5w+2=15w-10 | | 2x-2=24 | | 6x+152+3x+91=180 | | 3x+10+x-30=180 | | x^2-3x-150=0 | | .07x+.08(4x+32000)=46630 | | 4w*3w+2w=24 | | 25x+6-27x=4-6 | | 2(2b-4)=10-2b | | 11x+9=13(11-x) | | 10y=12-4x | | .5x+10=20 | | (36x^2)-120x=-70 | | -31y=434 | | 14=7x-4+2x | | 5+2(x+8)=-3 | | 19.72+6.5z=4.8z | | 32x+3=40x-3 | | 4x-16=24 | | 15-4x=x-5 | | (8x-10+8x-10)+(6x+6x)= | | 250+16x=210+18x | | 15d-8=2d | | (36x^2)-120=-70 | | 5h+2g=23 | | -14.8+0.2s=-16.4s+19.85+18.7s | | 8-5(2a+3)= | | y=-9-2x | | 8z-1=3z+6 | | |3-2b|=-7 | | |3-2b|=7 | | 8-y=5 | | 70x-35=245 | | 5x+12-2x=36+6x-7x | | -4(x+2)-11=2(-2x-3)-14 | | -15.73-9.3b=16.82-7.2b | | x-3x-150=0 | | 3y+48y=0 | | 3.9k=2.1k+17.1 | | 8=3x+4x-6 | | 11(p-5)-10(6p+22)=-32+38 | | -4y-15=0 | | -2.6r=1.7r+18.92 | | n-9=162 | | (5x+5x)+(3x+6+3x+6)= | | t^2+3t-40=0 | | a+17=4 | | 3*y-7=27 |


Related pages


simplify square root of 2250.875 in fraction550 in roman numeralsxp xqwhat is 5 of 213x 4y4n32cos53prime factorization of 58secx cosx 1what is the prime factorization of 105y7ycanoncityschools org1993 in roman numerals2.71828derivative of sin 5x2x 5y 4prime factorization 135sinkxderivative of ln2solve ax2 bx c 0simplify square root of 147derivative of sin 2x 2y sin 3x0.25 as a decimalderivative of 1 sinxsquare root of 5184divide by fraction calculatorgraph the equation y 2x 4algebra calculater0.6 as a decimalprime factors of 495prime factorization 13274 in roman numerals180-1354x 6yaddition of mixed fractions calculatorwhat does gcfwhat are prime factors of 565x 2y 79x-7i 3 3x-7u3.141592655x5 solutionsimplify 2x 2x2-2x-631965 in roman numeralsthe square root of 529what is pv nrtprime factorization of 162xci roman numeralswhat is the prime factorization of 11935cm to inchescsc2x 12ky0.375 as fractionprime factorization 37derivative of sin 3t2x 4y 616 qt to gal40 000 pounds to dollarsget easy solution expression calculatorcos4pifactor 3x 2-7x-624-101step by step equation solverprime factorization of 97factor 2x 2 13x 154x2 4x 1prime factorization of 57gcf of 54 and 63what is the prime factorization of 1205kg poundssolve cos 2xsystem of equations calculator with steps